2020
DOI: 10.1177/2325967120912427
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Outcomes After Primary ACL Reconstruction and Meniscus Ramp Repair

Abstract: Background: Satisfactory outcomes have been reported after all-inside meniscus ramp repair with combined anterior cruciate ligament reconstruction (ACLR). However, clinical outcomes after ACLR with inside-out meniscus ramp repair are limited.Purpose/Hypothesis: The purpose of this study was to evaluate patient-reported outcomes for patients who underwent ACLR and medial meniscus ramp repair compared with those who underwent isolated ACLR; patients in the 2 groups were matched for age, sex, and sport/activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(82 citation statements)
references
References 31 publications
2
80
0
Order By: Relevance
“…They noted that these extended lesions had a high failure rate (11.7%) of secondary meniscal surgery. DePhillipo et al 7 documented a 2% rate of secondary meniscectomy at a mean 33.6 months after inside-out ramp repair, and they recommended inside-out repair of all unstable ramp lesions at the time of ACL reconstruction. In the current study, the failure rate of the posterior portion was 7.1% (8/113) and that of posterior to midportion was 8.0% (7/ 87), and no significant difference was detected.…”
Section: Discussionmentioning
confidence: 99%
“…They noted that these extended lesions had a high failure rate (11.7%) of secondary meniscal surgery. DePhillipo et al 7 documented a 2% rate of secondary meniscectomy at a mean 33.6 months after inside-out ramp repair, and they recommended inside-out repair of all unstable ramp lesions at the time of ACL reconstruction. In the current study, the failure rate of the posterior portion was 7.1% (8/113) and that of posterior to midportion was 8.0% (7/ 87), and no significant difference was detected.…”
Section: Discussionmentioning
confidence: 99%
“…MRL repair failure after ACLR is remarkably lower in inside-out sutures (2%) than in all-inside (11%), which was recorded by another research group. 48 However, an earlier comparative study with a higher level of evidence showed that there is no statistical difference in healing status between these two techniques following ACLR. 49 Some studies claim that small and stable MRL does not have to be sutured.…”
Section: Arthroscopy and Repairmentioning
confidence: 98%
“…They also found that anterior laxity was significantly greater in the knees with unhealed ramp lesions compared with the knees in which the ramp lesions had healed. 30 DePhillipo et al 24 have shown that patients with combined ACL tear and ramp lesions have increased preoperative knee anteroposterior and rotational knee laxity, as demonstrated by grade 3 Lachman (44% vs 6%) and pivotshift (38% vs 12%) tests when compared with ACL tear group without ramp lesion (P .005 for both). Thus, it makes more sense to repair the ramp lesion to restore the physiological knee stability and kinematics.…”
Section: See Related Article On Page 2921mentioning
confidence: 98%
“…[18][19][20] In clinical practice, the rate of ramp lesions in ACLinjured knees has been reported to vary between 10% and 30% [21][22][23][24] with an increased frequency in chronic ACL injuries and in revision ACL reconstruction. [21][22][23][24][25] These findings contribute to the hypothesis that ramp lesions do not heal spontaneously and also raises questions about whether it is the failed graft that leads to a new ramp lesion or vice versa. Thus, I would again like to press upon the readers the importance of systematic exploration of the posteromedial compartment of the knee during arthroscopic ACL reconstruction (Fig 1), even if the initial probing from anterior of the posterior horn of the medial meniscus is normal.…”
Section: See Related Article On Page 2921mentioning
confidence: 99%
See 1 more Smart Citation